A novel role for Hsc70–4 in blood cell differentiation in Drosophila - Kharrat, Bayan; Gábor, Erika; Vilmos, Péter; Goins, Lauren M.; Honti, Viktor (Frontiers in Immunology, 2025)
The Drosophila lymph gland serves as an excellent model for studying blood cell development, closely mirroring the key components of mammalian hematopoietic niches: blood cell progenitors, mature blood cells, and niche cells that secrete signals to regulate progenitor maintenance. In the Drosophila larva, two primary types of mature hemocytes exist: macrophage-like plasmatocytes and platelet-like crystal cells. In cases of immune challenge or neoplastic conditions, a third type of hemocyte, the lamellocyte, appears to encapsulate large invaders that plasmatocytes cannot phagocytose. Importantly, the spontaneous appearance of lamellocytes in unchallenged larvae indicates defects in progenitor maintenance or blood cell fate regulation. In this study, we uncover a novel role for the molecular chaperone Hsc70–4 in suppressing lamellocyte differentiation across all three domains of the lymph gland. We show that Hsc70–4 depletion in the niche induces non-apoptotic cell death and oxidative stress, which in turn drives non-cell-autonomous lamellocyte differentiation via the Akt/Foxo pathway. In blood cell progenitors, particularly distal progenitors, Hsc70–4 loss promotes cell-autonomous lamellocyte differentiation, thereby diminishing the progenitor pool. Furthermore, silencing Hsc70–4 in mature hemocytes elicits a strong immune response characterized by primary lobe disintegration, lamellocyte transdifferentiation, and melanotic tumor formation. Together, these findings highlight the multifaceted roles of Hsc70–4 in Drosophila hematopoiesis, offering valuable insights that could enhance our understanding of the role of its orthologue in mammals and humans.